ANALISIS PROSES PENGAMBILAN KEPUTUSAN KONSUMEN PADA PERILAKU PEMBELIAN PRODUK YAMAHA MIO DI KOTA AMBON - Erlinda Tehuayo (Fakultas Ekonomi dan Bisnis Universitas Pattimura, 2018)
Marketing is one of the main activities carried out by entrepreneurs in their efforts to maintain their survival, to develop and to get profits as expected so that the company's business runs smoothly and get a positive character from consumers, then marketing activities must be able to fulfill the desires from consumers, then marketing activities must be able to fulfill the desires of consumers. Thus the task of a marketer is to examine the needs of consumers who are always changing and affect the company to adjust the combination of production in the form of goods and services to the needs needed.The consumer behavior model can be seen from the decision making process, where in the process of decision making this is influenced by external factors and internal factors in the process input stage. Through this research, it is expected that it can provide a clear picture of the process of product purchasing decisions through the needs recognition stage, information retrieval, evaluation of alternatives, purchasing decisions and post-purchase behavior towards Yamaha Mio products, especially in Ambon City. This can also be used as material for consideration to determine the next marketing strategy for the company concerned.The process of making consumer purchasing decisions on Yamaha Mio products through five stages, namely: introduction of needs, information retrieval, evaluation of alternatives, purchases and post-purchase behavior. The majority of respondents bought Yamaha Mio products because of work requirements. The majority of information sources in purchasing Yamaha Mio products are TV advertisements. In the alternative evaluation phase the main criteria for purchasing Yamaha Mio products are brands. The majority of respondents admitted being satisfied using Yamaha Mio productsKeywords: Process of making Consumer Purcasing Decisions, Consumer purcasing behavior